The determinants that affect government bond yield in Malaysia / Natasha Zulkifli - Zulkifli, Natasha (2022)
A government bond is a debt security issued by a government to support government spending and country development. Before investing in government bonds, investors need to assess with several factors such inflation risk, government debt, gross domestic product, and exchange rate risk. Government bond always be considered as risk free and traded in highly liquid market. in other perspective, government bond return is typically low rate of return. The purpose of this study is identifying the determinants that government bond yield in Malaysia. The dependent variable is government bond yield, and the independent variables are inflation rate, gross domestic product, government debt and exchange rate. The study is conducted by using time series data analysis. The data have been taken from 2012-2020 in quarterly basis which there are 36 observations in this research. The data has been taken from Data Stream, World bank and Bank Negara Malaysia (BNM). The tools that used in measure and analyze the data is by E-views software. Based on the previous research, several factors have significant impact on government bond yield. This study will focus on Malaysia.